Osteochondral Lesions in Pediatric and Adolescent Patients - Ghahremani, Shahnaz; Griggs, Rachel; Hall, Theodore; Motamedi, Kambiz; Boechat, M. Ines (Seminars in Musculoskeletal Radiology, 2014)
Osteochondral lesions are acquired, potentially reversible injuries of the subchondral bone with or without associated articular cartilage involvement. Injury results in delamination and potential sequestration of the affected bone. Although an association with mechanical and traumatic factors has been established, the etiology remains poorly understood. These lesions commonly occur in the knee; articular surfaces of the elbow, ankle, hip, and shoulder are also affected. Osteochondral lesions are relatively common in children and adolescents, and the incidence is increasing. Prognosis of these lesions depends on stability, location, and size of the lesion.Imaging has an essential role in the diagnosis, staging, and management of osteochondral lesions. Many of these lesions are first diagnosed by plain film. MRI adds value by identifying unstable lesions that require surgical intervention. This review focuses on the clinical and imaging features of osteochondral lesions of the knee, elbow, and ankle. Imaging criteria for staging and management are also reviewed.
Keywords: OCD; MRI; plain radiographs; knee; elbow; talus